2013
DOI: 10.1590/1414-431x20132938
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-mediated knockdown of FANCF suppresses cell proliferation, migration, invasion, and drug resistance potential of breast cancer cells

Abstract: Fanconi anemia complementation group F protein (FANCF) is a key factor, which maintains the function of FA/BRCA, a DNA damage response pathway. However, the functional role of FANCF in breast cancer has not been elucidated. We performed a specific FANCF-shRNA knockdown of endogenous FANCF in vitro. Cell viability was measured with a CCK-8 assay. DNA damage was assessed with an alkaline comet assay. Apoptosis, cell cycle, and drug accumulation were measured by flow cytometry. The expression levels of protein we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In the current study, an in vivo rabbit model of MI/R was established using protocols described in previous studies ( 40 , 41 ). Subsequently, the activities of SOD, LDH, CK-MB, MDA and troponin I/T in serum samples from each treatment group were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, an in vivo rabbit model of MI/R was established using protocols described in previous studies ( 40 , 41 ). Subsequently, the activities of SOD, LDH, CK-MB, MDA and troponin I/T in serum samples from each treatment group were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, down-regulation of miR-29a promoted the invasion of oral squamous cell carcinoma cells and tumor cell resistance [16]. Zhao et al found that inhibition of Fanconi anemia complementation group F protein increased the sensitivity of breast cancer cells to doxorubicin and resulted in decreased migration and invasion of tumor cells [17]. The epithelial mesenchymal transition (EMT) was also reported to be associated with drug resistance [17].…”
Section: Discussionmentioning
confidence: 99%
“…[5] Anti-inflammatory properties of statins in the treatment or prevention of PAH in patients with COPD were also highlighted. [91417] The beneficial effects of stains are also highlighted in a systematic review and meta-analysis of observational studies that emphasized a clear benefit of statins for patients suffering from COPD. [18] An in vitro study has shown that by inhibiting 3-hydroxy-3-methylglutaryl coenzyme A reductase, atorvastatin lowered concentrations of several inflammatory molecules including IL-6 derived from basal-state endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This may be an important anti-inflammatory property of statins in the treatment or prevention of PAH in patients with COPD. [9]…”
Section: Introductionmentioning
confidence: 99%